Óleo essencial das partes aéreas de Conyza bonariensis (L.) Cronquist (Asteraceae) : caracterização química, efeito antimelanoma in vitro e toxicidade em modelo de peixe-zebra - Ferreira, Rafael Carlos (2023)
Conyza bonariensis (L.) Cronquist (Asteraceae) is a plant rich in essential oils that exhibit antitumor effects and significant variations in their composition. This study aimed to obtain, characterize, and investigate the antitumor and toxicological effects of the essential oil from C. bonariensis aerial parts (OECB) collected at the Medicinal Plants Garden of the Institute of Pharmaceutical and Medicinal Research (IPeFarM/UFPB). The OECB was obtained by hydrodistillation using a Clevenger-type apparatus and analyzed by gas chromatography-mass spectrometry (GC-MS). Cytotoxicity was assessed using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay on human tumor cell lines (SK-MEL-28, HeLa, HCT-116, HL-60, and K562) and non-tumor (HaCaT) cells. Different signaling pathways associated with OECB cytotoxicity were evaluated in silico and in vitro. Additionally, OECB toxicity was investigated in a zebrafish model. The major component was the (Z)-2-lacnofilum ester (EZ) (57.24%). After 72 hours of treatment, the SK-MEL-28 melanoma cell line was the most sensitive to OECB cytotoxicity (half-maximal inhibitory concentration – IC50 = 18.65 ± 1.16 μg/mL). In the healthy human keratinocyte cell line HaCaT, an IC50 of 56.49 ± 1.03 μg/mL was obtained, showing three times greater selectivity for the SK-MEL-28 line. Thus, the mechanisms of action of OECB were investigated in this tumor cell line. Cell cycle analysis showed a significant increase in the sub-G1 fraction after 48 hours of OECB treatment, and annexin V-FITC/PI staining revealed an increase in the percentage of apoptotic cells. Additionally, confocal laser microscopy showed morphological features of apoptosis. OECB stimulated the production of Reactive Oxygen Species (ROS) after 30 min, 1 h, or 3 h of treatment, and pre-treatment with N-acetyl-L-cysteine (NAC) significantly prevented its cytotoxicity. In molecular docking, EZ exhibited molecular interactions with the active sites of ERK1, JNK1, p38α MAPK, PKB/AKT, and NF-κB proteins. Using specific antibody labeling, a significant increase in the percentage of cells labeled with anti-ERK1/2, anti-JNK1/2, anti-PKB/AKT, and anti-NF-κB antibodies was observed after 48 hours of OECB treatment, along with a significant reduction in the number of cells labeled with anti-p38 MAPK. Furthermore, pre-treatment with ERK1/2 or JNK inhibitors prevented OECB cytotoxicity, while the p38 MAPK inhibitor potentiated this effect. In the zebrafish model, OECB (1.5 μg/mL) induced the death of all embryos, and non-lethal effects were observed at concentrations from 0.50 to 1.25 μg/mL. Additionally, a significant increase in the activity of enzymes associated with oxidative stress (GPx, GST, CAT, LDH) and a reduction in AChE were observed. In summary, OECB exhibits in vitro antimelanoma effects through the induction of apoptosis, oxidative stress, inhibition of p38 MAPK, and activation of ERK1/2, JNK1/2, PKB/AKT, and NF-κB, as well as embryotoxicity in the zebrafish model.